Analisis Strategi Promosi Media Sosial Pada UMKM Coffee Shop (Studi Kasus Markoka Café Pangkalpinang) - Mailani, Mery; Tasyah, Tasyah; Pratama, M.Tafril; Noviyanti, Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this research is to examine how Micro, Small, and Medium Enterprises (MSMEs) in the coffee shop industry, specifically Markoka Cafe Pangkalpinang, utilize social media marketing. The research method employed a descriptive qualitative approach with data collection techniques including direct observation, interviews with business owners, and promotional documentation. The results indicate that Markoka Cafe actively utilizes social media such as Instagram and WhatsApp as digital marketing tools. This strategy is effective in increasing consumer engagement and brand awareness, thereby strengthening Markoka Cafe's position in the local Pangkalpinang coffee shop market and enhancing business exposure and interaction with customers.